Diversity and Pluralism: An Economist's View - Nicola Genovese; Maria Grazia La Spada (Fondazione Eni Enrico Mattei (FEEM), 2006)
The problems about diversity concern various themes. We will show that the economic theory can contribute by itself to the debate in progress. It could seem paradoxical, but what is called the dismal science can serve to attenuate some pessimistic attitudes, putting in prominence a perspective for humanity which is desired. To introduce such contribution, we have examined some essential characteristics of neoclassic theory, regarding the typical features of the individual which it assumes and the principle of rationality. Our analysis emphasizes the importance of the economy of market which prevails on other economic systems and makes possible the realization of a culturally sustainable development. It also examines the economic benefits of diversity both on the function production and the possibility to have a dynamic demand of goods. The difference between integration and homogenization will be treated and also the importance of international commerce and direct investments.
Keywords: D2; O3; O31; 330; Neoclassical Theory and Diversity; Productive Benefits of Ethnic Diversity; Cultural Pluralism; Neoklassik; Marktwirtschaft; Kultur; Ethnische Gruppe; Ethnische Beziehungen